(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: One of the most complex problems facing pregnant women is Abortion, which affects approximately 15% of registered pregnancies in most of the world’s population, there are many reasons that lead to miscarriages, some of which are known and studied, and they are many and varied, but 50% of these cases remain unexplained scientifically. Materials and Methods: Samples were collected from both Al-Manathira Hospital and some private clinics during the period from 10/1/2022 to 3/1/2023, to conduct studies on (pregnant and healthy women) 50 women suffering from spontaneous abortion and control group, the number of which was (30) women. Women who were naturally pregnant during the pregnancy period between (2-6) months without having previously experienced Abortion were considered a control group, each woman’s weight and height were measured to determine her (BMI). Results: The findings of this study revealed a significant decline (p<0.05) in BMI for women who had Abortion. Biochemical tests also showed a significant decrease (p<0.05) in the levels of prolactin and progesterone in women who had Abortion compared to the control, However, the results indicated a notable rise in estrogen levels in women who had an abortion. Conclusion: The findings indicate that disturbances in body mass index (BMI), whether through excess or deficiency, can negatively affect pregnancy stability. Moreover, abnormalities in prolactin and progesterone levels are associated with impaired endometrial support and an increased risk of miscarriage. In contrast, excessive elevation of estrogen may induce uterine contractions and further contribute to pregnancy loss.